Technological Innovations for Water Quality Management in Marine and Brackish Aquaculture: A Scoping Review (SDG 6 & SDG 14) - sungkawati, endang; Shumaila, Shumaila (Assyfa Journal Scientific Essay, 2025)
This study is conducted because water quality is a crucial factor in the sustainability of marine and brackish aquaculture, which faces various environmental challenges and the need for increased production. The main objective of this research is to map and review the latest technological innovations used for water quality management in such aquaculture, particularly in the period 2022–2025. The method used is a scoping review of scientific literature discussing sensor-based technologies, biofilters, and integrated water management systems. The study results indicate that these innovations are effective in reducing water pollution, enhancing fish health, and strengthening the resilience of aquatic ecosystems. Furthermore, the application of these technologies significantly contributes to achieving Sustainable Development Goals SDG 6 (Clean Water and Sanitation) and SDG 14 (Life Below Water). The conclusion of this study emphasizes that widespread adoption of water quality management technologies is crucial to expanding and successfully sustaining aquaculture. Thus, these innovative technologies not only support sustainable fishery production but also preserve the aquatic environment, which is the foundation of marine life and the coastal community's economy.